MENGKONSUMSI BUAH SEMANGKA DALAM MENURUNKAN HIPERTENSI PADA IBU HAMIL DI DESA DAMAKURAT KEC. SIPISPIS KAB. SERDANG BEDAGAI TAHUN 2022 - FERIKA DESI; DEWI SRI RAHAYU TINENDUNG (JURNAL ILMIAH KOHESI, 2022)
Pregnancy is a period that greatly determines the quality of future human resources, because the growth and development of children is very much determined by the condition of the fetus in the womb. Because pregnant women require a higher nutritional adequacy rate (RDA) than women who are not pregnant. Pregnant women must have a healthy lifestyle. Such as eating nutritious food, getting enough exercise, resting, and avoiding alcohol and not smoking. Watermelon has a higher potassium content than cucumber. Some of the content of anti-hypertensive drugs that can be found in watermelon are beta carotene, potassium, calcium, water content and amino acids that can keep blood pressure normal. This study aims to determine the benefits of consuming lots of watermelon in pregnant women in reducing hypertension in the village. Damakurat District. Sipispis Kab. Serdang Bedagai in 2021. The type of research used is a pre-experimental research with a one group pre-post test design. The population in this study were all pregnant women in Damakurat Village. The sampling technique used Accidental Sampling with a sample size of 20 people. Data collection with SOP Questionnaire instrument. Data analysis used the Wilcoxon Sign Rank Test with a significant level of p <0.05). The results of the analysis show that there are benefits of consuming lots of watermelon for pregnant women in reducing hypertension in Damakurat Village, Kec. Sipispis Kab. Serdang Bedagai with a value of P = 0.001 where P = <0.05. It is suggested that this study can be used as a source of information for pregnant women to continue consuming watermelon as an alternative treatment that is cheap, easy, and practical in reducing blood pressure in patients with hypertension in pregnant women